2006
DOI: 10.1021/bi061860g
|View full text |Cite
|
Sign up to set email alerts
|

Pyridoxamine Analogues Scavenge Lipid-Derived γ-Ketoaldehydes and Protect against H2O2-Mediated Cytotoxicity

Abstract: Isoketals and levuglandins are highly reactive γ-ketoaldehydes formed by oxygenation of arachidonic acid in settings of oxidative injury and cyclooxygenase activation, respectively. These compounds rapidly adduct to proteins via lysyl residues, which can alter protein structure/function. We examined whether pyridoxamine, which has been shown to scavenge α-ketoaldehydes formed by carbohydrate or lipid peroxidation, could also effectively protect proteins from the more reactive γ-ketoaldehydes. Pyridoxamine prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
78
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(82 citation statements)
references
References 64 publications
4
78
0
Order By: Relevance
“…The data obtained support our previous fi ndings that Lys 358 and Lys 476 are both targets of iso [4]LGE 2 adduction in CYP27A1 ( 23 ). Our results also strengthen interpretations from other reports on isoLG-associated loss of enzyme activity ( 29,41,(54)(55)(56) and demonstrate that posttranslational protein modifi cation by isoLGs is not simply a biomarker but is in fact a mechanism by which oxidation of lipids leads to modulation of enzyme activity. It should be noted, then, that in retinal mitochondria, the targets for isoLG adduction may not be limited to CYP27A1.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The data obtained support our previous fi ndings that Lys 358 and Lys 476 are both targets of iso [4]LGE 2 adduction in CYP27A1 ( 23 ). Our results also strengthen interpretations from other reports on isoLG-associated loss of enzyme activity ( 29,41,(54)(55)(56) and demonstrate that posttranslational protein modifi cation by isoLGs is not simply a biomarker but is in fact a mechanism by which oxidation of lipids leads to modulation of enzyme activity. It should be noted, then, that in retinal mitochondria, the targets for isoLG adduction may not be limited to CYP27A1.…”
Section: Discussionsupporting
confidence: 90%
“…Despite similar reactivity, the enzyme activity. IsoLG-mediated loss of enzyme activity has been reported before ( 29,41,(54)(55)(56), however, the evidence provided were indirect. In the pioneering study of Fukuda et al ( 54 ), isoLG-treated HEK-293 cells and cultured atrial HL-1 myocytes showed reduced electrophysiology recordings, but isoLG modifi cation of the cardiac sodium channels responsible for this dysfunction was not shown.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In vivo, IsoLGs are formed during inflammation, either through increased formation of prostaglandins and re-arrangement of the PGH 2 intermediate formed by cyclooxygenase [23], or during oxidative stress [24,25]. Consistent with this observation, circulating and tissue levels of IsoLGs adducts are increased in multiple disease conditions associated with both, including end-stage renal disease and atherosclerosis [26], hypertension [27], pulmonary fibrosis [22].…”
Section: Longatomentioning
confidence: 75%